Enhanced proton conduction of crystalline organic salt hybrid membranes and the performance of fuel cells. (6th October 2022) - Yang, Yan; Chen, Xu-Yong; Li, Xin-Mei; Zhao, Fang; Bai, Xiang-Tian; Cao, Li-Hui
Abstract : The hybrid Nafion membranes of a hydrogen-bonded crystalline organic salt material are used for proton conduction and proton exchange membrane fuel cell applications. Abstract : Among the components of a proton exchange membrane fuel cell (PEMFC), the proton exchange membrane (PEM) is an essential constituent part of the fuel cell. Here, a crystalline organic salt (HCOS-1 ) with amino and sulfonate groups has been synthesized. HCOS-1 exhibited a high proton conductivity of 3.23 × 10 −3 S cm −1 at 100 °C and 93% relative humidity (RH). In order to improve its proton conductivity, HCOS-1 was blended with Nafion to prepare a composite membrane. At 100 °C and 98% RH, the composite membrane containing 6 wt% HCOS-1 exhibits a higher proton conductivity of 7.24 × 10 −3 S cm −1, which is more than twice compared with 3.35 × 10 −3 S cm −1 of the recast Nafion membrane. Compared with the recast Nafion membrane, the maximum power density of the hydrogen–oxygen fuel cell using the 6 wt% HCOS-1 composite membrane at 80 °C and 100% RH has increased by 9.95%, from 815 mW cm −2 to 896 mW cm −2 .